Heat Resistance of Salmonella: the Uniqueness of Salmonella senftenberg 775W - Ng, Henry (1969)
Of approximately 300 cultures of Salmonella, representing 75 different serotypes, none was found to be as heat-resistant as S. senftenberg 775W. However, S. blockley 2004 was 5 times more heat-resistant and S. senftenberg 775W was 30 times more heat-resistant than S. typhimurium Tm-1, the reference strain in this study. All other strains of Salmonella tested, including 19 strains of S. senftenberg and 7 strains of S. blockley, had decimal reduction times at 57 C of about 1 min, equivalent to that of the reference organism, Tm-1. As observed in other bacterial species, strain 775W is more heat-sensitive in the log phase than in the stationary phase of growth. Cells from cultures grown at 44 C were more heat-resistant than those grown at either 35 or 15 C; the medium of growth, whether minimal or complex, made no appreciable difference in heat resistance. Cells from cultures limited by a carbon source were killed at a much slower rate than those limited by a nitrogen source and exhibited a 1-hr lag at 55 C before a significant rate of kill was attained. For any given set of growth conditions, strain 775W was always more heat-resistant than another strain of S. senftenberg, 197B, which has normal heat resistance.